Sex‐specific Differences of the Infraacetabular Corridor: A Biomorphometric CT‐based Analysis on a Database of 523 Pelves. Issue 1 (January 2015) - Gras, Florian; Gottschling, Heiko; Schröder, Manuel; Marintschev, Ivan; Reimers, Nils; Burgkart, Rainer
Abstract: Background: An infraacetabular screw path facilitates the closure of a periacetabular fixation frame to increase the plate fixation strength in acetabular fractures up to 50%. Knowledge of the variance in corridor sizes and axes has substantial surgical relevance for safe screw placement. Questions/purposes: (1) What proportion of healthy pelvis specimens have an infraacetabular corridor that is 5 mm or larger in diameter? (2) Does a universal corridor axis and specific screw entry point exist? (3) Are there sex‐specific differences in the infraacetabular corridor size or axis and are these correlated with anthropometric parameters like age, body weight and height, or the acetabular diameter? Methods: A template pelvis with a mean shape from 523 segmented pelvis specimens was generated using a CT‐based advanced image analyzing system. Each individual pelvis was registered to the template using a free‐form registration algorithm. Feasible surface regions for the entry and exit points of the infraacetabular corridor were marked on the template and automatically mapped to the individual samples to perform a measurement of the maximum sizes and axes of the infraacetabular corridor on each specimen. A minimum corridor diameter of at least 5 mm was defined as a cutoff for placing a 3.5‐mm cortical screw in clinical settings. Results: In 484 of 523 pelves (93%), an infraacetabular corridor with a diameter of at least 5 mm was found. Using the mean axis angulations (54.8° [95% confidence interval CI, 0.6] from anterocranial to posterocaudal in relation to the anterior pelvic plane and 1.5° [95% CI, 0.4] from anteromedial to posterolateral in relation to the sagittal midline plane), a sufficient osseous corridor was present in 64% of pelves. Allowing adjustment of the three‐dimensional axis by another 5° included an additional 25% of pelves. All corridor parameters were different between females and males (corridor diameter, 6.9 [95% CI, 0.2] versus 7.7 [95% CI, 0.2] mm; p < 0.001; corridor length, 96.2 [95% CI, 0.7] versus 106.4 [95% CI, 0.6] mm; p < 0.001; anterior pelvic plane angle, 54.0° [95% CI, 0.9] versus 55.3° [95% CI, 0.8]; p < 0.01; sagittal midline plane angle, 4.3° [95% CI, 0.6] versus −0.3° [95% CI, 0.5]; p < 0.001). Conclusion: This study provided reference values for placement of a 3.5‐mm cortical screw in the infraacetabular osseous corridor in 90% of female and 94% of male pelves. Based on the sex‐related differences in corridor axes, the mean screw trajectory is approximately parallel to the sagittal midline plane in males but has to be tilted from medial to lateral in females. Considering the narrow corridor diameters, we suggest an individual preoperative CT scan analysis for fine adjustments in each patient.